Comparative Empirical Analysis of Financial Failures of Enterprises with Altman Z-Score and VIKOR Methods: BIST Food Sector Application - Mehmet Apan; Ahmet Öztel; Mehmet İslamoğlu (Australasian Accounting, Business and Finance Journal, 2018)
This study includes an empirical review of the financial failure of enterprises. For the empirical analysis, 2008-2014 period data for enterprises operating in the Food and Drink Sector traded on BIST (Borsa Istanbul), were used. The financial failures of these enterprises were first determined according to the Altman Z-Score method, and the financial success rankings of the enterprises were then determined by the VIKOR (VIseKriterijumsa Optimizacija I Kompromisno Resenje) method, which is one of the MCDM (Multiple Criteria Decision-Making) methods. The empirical analysis results obtained from these two different methods have been comparatively evaluated and interpreted. In this study, the VIKOR method is suggested as an alternative method for financial failure analysis.
Keywords: Altman Z-Score; VIKOR; Financial Failure; Borsa Istanbul-Food; Beverage Index (BIST XGIDA)